Prix versus quantités : les contorsions du marché du carbone européen - Nathalie Berta (Revue de la Régulation)
The European carbon market has been created to set a price to carbon emissions and to drive investments into low carbon technologies. Since its creation in 2015, and despite the successive cap restrictions, it experienced very low and volatile prices and thus failed to provide the expected incentives. As a consequence, the European Commission adopted several reforms, the main one being the creation of a market stability reserve. All these reforms try to control the price, but in an indirect way, through adjustments of the allowances supply. As a cap-and-trade instrument, the European market guaranties that the total emissions will not overtake the issued allowances — the cap. The trade is justified by the cost-effectiveness of the competitive allocation that it is supposed to reach. But contrary to a tax system, price uncertainty is intrinsic to allowances markets, to quantities instruments. Creating a competitive market because of the expected efficiency of its price setting and then trying ex post to regulate the price seems rather paradoxical. Furthermore, since this market is above all a financial market driven by derivatives, achieving price stability through ex post supply adjustments is a wild hope. Only a tax could provide the expected price stability.